Masculinity in the Song Lyrics of Imagine Dragons: How it is represented - Fatrisia Hasan; Muzdalifah Mahmud; Kartin Lihawa (Journal of Language Education (JoLE), 2024)
This study examines the representation of masculinity in the song lyrics of Imagine Dragons through a semantic analysis approach. Using Lyons' (1981) theory of contextual meaning and Chafetz's (1978) theory of masculinity, the research identifies how the contextual meaning representing masculinity is conveyed in three selected songs: Demons (2012), Thunder (2017), and Eyes Closed (2024). The findings based on contextual analysis reveal five categories of masculinity: other personality traits, interpersonal thinking, intelligence thinking, emotional control, and sexual aggression. The study highlights that Imagine Dragons' lyrics often reflect traditional masculinity values such as ambition, independence, resilience, and emotional restraint, with an emphasis on personal struggles and self-discovery. The results contribute to the understanding of masculinity in contemporary Western popular music and its impact on gender representation. Keywords: contextual meaning, Imagine Dragons, masculinity, semantics, song lyrics